Coaxially-structured fibres with tailored material properties for vascular graft implant. - Johnson, R.; Ding, Y.; Nagiah, N.; Monnet, E.; Tan, W.
Readily-available small-diameter arterial grafts require a great combination of materials properties, including high strength, compliance, suturability, blood sealing and anti-thrombogenicity, as well as anti-kinking property for those used in challenging anatomical situations. We have constructed grafts composed of coaxially-structured polycaprolactone (PCL)/gelatin nanofibres, and tailored the material structures to achieve high strength, compliance and kink resistance, as well as excellent water sealing and anti-thrombogenicity. Coaxially-structured fibres in the grafts provided mechanical stability through the core, while flexibility and cell adhesion through the sheath. Results showed that graft compliance increased while strength decreased with the concentration ratio between core and sheath polymers. Compared to pure PCL fibrous surfaces, coaxial PCL/gelatin fibrous surfaces potently inhibited platelet adhesion and activation, providing excellent anti-thrombogenicity. To render sufficient burst strength and suturability, an additional layer of pure PCL was necessary to cap the layer of coaxial PCL/gelatin fibres. The two-layered grafts with the wall thickness comparable to native arteries demonstrated artery-like compliance and kink resistance, properties important to arteries under complex mechanical loading. The in vivo evaluation was performed using the interposition carotid artery graft model in rabbits for three months. Interestingly, results from ultrasonic imaging and histological analysis demonstrated that the two-layered grafts with a thinner outer PCL layer, which possessed higher compliance and kink resistance, showed increased blood flow, minimal lumen reduction and fibrosis. All vascular grafts exhibited patency and induced limited cell infiltration. Together, we presented a facile and useful approach to fabricate vascular grafts with superior graft performances, biomechanical properties, and blood compatibility. Grafts with artery-like compliance and flexibility have demonstrated improved implantation outcomes.
Keywords: COAXIAL ELECTROSPINNING; GELATIN; NANOFIBRES; VASCULAR TISSUE; ENGINEERED SCAFFOLDS